(untitled) (Iranian Journal of Kidney Diseases, 2010)
Dialysis and transplantation are life-saving but very expensive treatments. Current increases in the number of hemodialysis centers, machines, shifts, and kidney transplantations cannot keep pace with the increasing number of end-stage renal disease patients globally. The only way to decrease the incidence of end-stage renal disease is identifying patients with low glomerular filtration rate. The risk groups to be targeted, the expected outcomes, and the tests to be ordered are reviewed in this article. The ways that it is possible to make a screening program sustainable and likely cost-efficient model is discussed. It seems the high-risk target population for chronic kidney disease screening in our country can be those with diabetes mellitus, hypertension, hyperlipidemia, age over 40 years, and obesity (possibly abdominal obesity). Macroalbuminuria check in addition to serum creatinine measurement in high-risk population may look a practical approach to initiate a national program.